Analisis Kinerja Keuangan Sebelum dan Setelah Akuisisi (Studi pada Perusahaan yang Terdaftar di BEI) - Andrian, Anthalucky Dewi; Listyowati, Listyowati (University of Merdeka Malang, 2019)
The purpose of this research is to find out the difference of financial performance of the acquirer which is measured by using net profit margin, return on asset, return on equity, total assets turnover, debt to equity ratio, current ratio, dan earning per share before and after acquisition. The data used were secondary data obtained from websites the Indonesia Stock Exchange. With the population used is a company that performs the acquisition and is listed on the stock exchange Indonesia. The sample collection technique has been done by using purposive sampling, so 16 companies which has carried out the acquisition. The data analysis technique has been done by performing Paired Sample t-test. Based on the result of the analysis which has been carried out by using paired sample t-test that 5 financial ratios have significant difference i.e.: net profit margin, return on equity, return on assets, total assets turnover dan earning per share. that are 2 financial ratios which do not have any significant differences i.e. Debt to equity ratio, dan current ratio which means that there are no significant differences in these two ratios